1991
DOI: 10.1093/oxfordjournals.humrep.a137343
|View full text |Cite
|
Sign up to set email alerts
|

XY-trivalent association and synaptic anomalies in a male carrier of a Robertsonian t(13;14) translocation

Abstract: Synaptonemal complexes were analysed in 91 pachytenes from a patient carrier of a Robertsonian translocation 45XY, t(13;14). Electron microscopic studies were carried out in 36 pachytenes. In some cases, sequential light microscopy/electron microscopic images were obtained (16/36). As the resolution of the light microscope does not allow an accurate characterization of anomalies, only EM images have been taken into account. Association of the trivalent and the sex vesicle was detected in 8 of 36 pachytenes (22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 0 publications
4
21
0
1
Order By: Relevance
“…This finding is consistent with previous published data [7-9, 11, 12, 17, 20]. The high prevalence of the alternate segregation had been presumed to occur because cis-configuration of the trivalent during meiosis favors an alternate segregation in all Rob translocations [21][22][23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous published data [7-9, 11, 12, 17, 20]. The high prevalence of the alternate segregation had been presumed to occur because cis-configuration of the trivalent during meiosis favors an alternate segregation in all Rob translocations [21][22][23].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were made previously by other studies [15][16][17]. This mechanism of meiotic non-disjunction for sex chromosomes may be the results of a non-random association at prophase I between the trivalent and the sex chromosomes [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…As a consequence, unpaired regions will appear; it has been suggested that these unpaired regions may interfere with the synaptic process of other bivalents, producing synaptic anomalies. 39,40 These abnormalities could produce meiotic arrest, but could also lead to the production of multiple aneuploidies (reviewed by Egozcue et al 38 ). Nevertheless, the variable frequency of aneuploidies reported among different control males reported by many authors, 41,42 and in infertile men 43 make necessary to consider our findings with caution, until the source of these variations can be clarified.…”
Section: European Journal Of Human Geneticsmentioning
confidence: 80%
“…Ta b l e 2 S i g n i f i c a n t b i v a l e n t p a i r s a s s o c i a t i o n s o f MI,22,XY,III(13q14q) (n = 41) and MI,22,XY,III(14q15q) (n = 15) Note: global mean = 0.152; 95 % CI = [0.147-0.157] a Significant bivalent pairs coinciding with those described in normal karyotypes [21] There are different non-mutually exclusive possibilities to explain such variations. Studies in Robertsonian translocation carriers have described that the reorganized chromosomes usually show asynaptic regions at pachytene which are often associated with asynaptic regions of other bivalents [40][41][42][43][44][45]. It has also been described that asynaptic regions suffer heterochromatinization and gene silencing [31,46].…”
Section: Discussionmentioning
confidence: 99%